2015
DOI: 10.1038/srep12241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nt-truncation and coexpression of isolated Nt domains on the membrane trafficking of electroneutral Na+/HCO3– cotransporters

Abstract: The SLC4 genes are all capable of producing multiple variants by alternative splicing or using alternative promoters. The physiological consequences of such diversity are of great interest to investigators. Here, we identified two novel variants of the electroneutral Na+/ cotransporter NBCn1, one full-length starting with “MIPL” and the other Nt-truncated starting with “MDEL”. Moreover, we identified a new promoter of Slc4a10 encoding NBCn2 and a novel type of Nt-truncated NBCn2 starting with “MHAN”. When hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…In rats, the Slc4a10 gene can give rise to multiple NBCn2 variants that fall into two major groups. Depending on the usage of different promoters, 15 the extreme Nt of these variants can begin either with MCDL (NBCn2-E/F/G/H) or MEIK (NBCn2-A/B/C/D). In the MCDL group, the rat kidney mainly expresses NBCn2-G, and in the MEIK group, it expresses mainly NBCn2-C. 14,15 Here, we find that MCDL-NBCn2 and MEIK-NBCn2 exhibit distinct tissue and subcellular distributions in rat kidney, with MCDL-NBCn2 being localized in the apical membrane of PTs, and MEIK-NBCn2 localized in the BLM of mTALs and IMCDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, the Slc4a10 gene can give rise to multiple NBCn2 variants that fall into two major groups. Depending on the usage of different promoters, 15 the extreme Nt of these variants can begin either with MCDL (NBCn2-E/F/G/H) or MEIK (NBCn2-A/B/C/D). In the MCDL group, the rat kidney mainly expresses NBCn2-G, and in the MEIK group, it expresses mainly NBCn2-C. 14,15 Here, we find that MCDL-NBCn2 and MEIK-NBCn2 exhibit distinct tissue and subcellular distributions in rat kidney, with MCDL-NBCn2 being localized in the apical membrane of PTs, and MEIK-NBCn2 localized in the BLM of mTALs and IMCDs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the rat kidney expresses two groups of full-length NBCn2 (Slc4a10) variants, differing in the amino termini (Nts), one starting with residue MCDL (mainly NBCn2-G), and the other with MEIK (mainly NBCn2-C). 14,15 Here, we report that MCDL-NBCn2 is expressed at the apical membrane of the PT, whereas MEIK-NBCn2 is expressed at the BLM of the medullary thick ascending limb (mTAL) and inner medullary collecting ducts (IMCDs). Systemic acid-base disturbances reciprocally regulate the abundances of MCDL-NBCn2 and NHE3.…”
mentioning
confidence: 99%
“…A series of studies have shown that the variable region Nt-VR1 is not necessary for the surface expression and transport activity of NCBTs (McAlear et al, 2006 ; Parker et al, 2007a ; Fukuda et al, 2013 ; Wang et al, 2015 ). When heterologously expressed in Xenopus oocytes, NBCn1-Q, a natural variant of Slc4a7 lacking Nt-VR1, contains minimal transport activity and typical Na + -conductance characteristic of NBCn1 (Wang et al, 2015 ). However, removal of the entire Nt domain almost completely inactivates rat NBCe1-C when heterologously expressed in Xenopus oocytes, although this molecular maneuver has little effect on the surface expression of NBCe1 (McAlear et al, 2006 ).…”
Section: Role Of Nt Domain In Slc4 Transportersmentioning
confidence: 99%
“…The alternative Nts arise from two different types of sources: (1) transcription using distinct promoters, e.g., the generation of alternative Nts of NBCe1-A vs. NBCe1-B (Abuladze et al, 2000 ); (2) alternative splicing of cassette exons in the 5′ portion of the messenger RNAs, e.g., the generation of alternative Nts of NBCn1-Q vs. NBCn1-R (Wang et al, 2015 ). Generally, the alternative Nts have little similarity among different SLC4 family members and different variants of the same member.…”
Section: Structural Variations In Slc4 Transportersmentioning
confidence: 99%
See 1 more Smart Citation